Surface modification of brick by zinc oxide and silver nanoparticles to improve performance properties. (February 2021) - Cheraghcheshm, Fatemeh; Javanbakht, Vahid
Abstract: Due to its versatility, durability, and mechanical stability, brick is an important construction material. In the current study, the brick surface was coated by ZnO nanoparticles based on chemical deposition and modified by silver nanoparticles to create a hydrophobic property on the brick surface as well as photocatalytic and antibacterial properties. The modified brick nanocomposite was characterized by FESEM, XRD, and UV–Visible and then, hydrophobicity, photocatalytic, and antibacterial properties were investigated. Suitable values of bandgap energy of 3.25 eV and 3.22 eV were obtained for the brick modified by ZnO and ZnO/Ag, respectively. By using the dye degradation test under UV irradiation, the brick modification significantly increased the photocatalytic property. The antibacterial property of the nanocomposite was investigated by the disk diffusion method based on staphylococcus aureus and bacillus cereus as gram-positive bacteria and Escherichia coli and pseudomonas aeruginosa as gram-negative bacteria and the experiments showed acceptable results. The results of flexural strength and efflorescence test showed that flexural strength of the brick modified by ZnO/Ag is almost 1.8 times more than non-coated brick and the modified brick represented less efflorescence on the surface. The results showed the improvement of the applicable properties of the brick. Highlights: The brick surface was modified by ZnO and silver nanoparticles to improve properties. Flexural strength and anti-efflorescence properties of the brick were enhanced. The antibacterial property the brick showed acceptable results.